Comparison of Outcomes in Critically Ill Patients Installed with Mechanical Ventilation Performed Early and Late Tracheostomy at Dr. M. Djamil General Hospital Padang - Rahmat Hidayat; Muhammad Riendra; Rahmat Taufik (HM Publisher, 2022)
Background: Tracheostomy is an alternative that is widely used as airway access after the use of a ventilator in the care of critically ill patients. Several factors are known to influence the outcome in patients undergoing tracheostomy. This study aimed to compare the outcomes of critically ill patients installed with mechanical ventilation performed early and late tracheostomy in Dr. M Djamil General Hospital, Padang, Indonesia. Methods: This study was an analytical observational study with a cross-sectional approach. A total of 97 research subjects participated in this study. Data analysis was carried out with the help of SPSS software in a univariate and bivariate manner between tracheostomy time (early and late) with patient outcomes in the form of death and length of stay. Results: There was a statistical difference in the mortality rate in critically ill patients with mechanical ventilation performed early and late tracheostomy, p = 0.014. There is a statistical difference in the length of stay in the intensive care unit in critically ill patients with mechanical ventilation performed early and late tracheostomy with p = 0.000. Conclusion: There are differences in outcomes in the form of mortality and length of stay in critically ill patients who have tracheostomy installed at Dr. M. Djamil General Hospital Padang, Indonesia.